Instructional Leadership in 21st Century of School Administrators Affecting of Academic Affairs Administration of Schools under Roi Et Primary Educational Service Area Office 1 - Yeesarapat , Pattanawit; Kamplae, Pattarawan; Chapanya, Yuvatida (Journal of Roi Et Rajabhat University, 2023)
The objectives of this research were to 1) examine the level of academic affairs administration in schools; 2) investigate the instructional leadership of school administrators in the twenty-first century; 3) examine the relationship between academic affairs administration and instructional leadership in the twenty-first century; and 4) investigate the impact of instructional leadership on academic affairs administration in schools. The research utilized a sample group consisting of 33 school administrators and 227 government instructors, totaling 310 individuals. Stratified random sampling was employed, classifying the individuals based on the size of their respective schools. The sampling table developed by Krejcie & Morgan was used for this purpose. The research was divided into three sections. Part 1 consisted of a checklist, while parts 2 and 3 involved a rating scale questionnaire with levels ranging from 1 to 5. The confidence value for part 2 was 0.91, and for part 3 it was 0.94. The statistics used in the data analysis were Percentage, Mean, and Standard Deviation. The statistics used to test the hypothesis were Pearson's Product Moment Correlation Coefficient and Stepwise Multiple Regression. The findings indicated that: 1) school administrators demonstrated a high level of instructional leadership in the 21st century, 2) the administration of academic affairs in schools also exhibited a high level of proficiency, 3) there was a strong positive correlation between the instructional leadership of school administrators in the 21st century and the administration of academic affairs in schools. The correlation coefficient reached a statistical significance at a level of .01, 4) the instructional leadership of school administrators in the 21st century has a significant impact on the administration of academic affairs in schools. This impact is manifested through four crucial aspects: defining a vision, goal, and mission for learning, fostering student development, promoting teacher development, and creating a conducive learning atmosphere. The four factors accurately predicted 84.50% of the variance in academic affairs administration of schools, with a statistical significance level of .01.